PENGARUH LITERASI KEUANGAN DAN PENGELOLAAN KEUANGAN TERHADAP LAPORAN KEUANGAN UMKM KAMPUNG KUE RUNGKUT LOR SURABAYA - Fitria Angelina; Ratih Dewi Titisari Haryana (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
Financial management is the most important task for business actors, especially micro-economic actors who often operate at the MSME level. To run their business, business actors must have financial literacy. The purpose of this study is "to determine the effect of financial management and the level of financial literacy on the financial reports of MSMEs in Kampung Kue Rungkut Lor, Surabaya. The research methodology used is a quantitative approach." The sampling technique used was the saturation technique with a sample size of 68 MSME actors. The questionnaire was sent as part of the research data collection technique using primary data. SPSS is a statistical program used to analyze data. Based on the results of the study, the financial reports of MSMEs in the Kampung Kue Rungkut Lor area of ​​Surabaya are significantly influenced by financial management and financial literacy, both partially and simultaneously.